Prospects of the baking industry - Petrova, Irina (My University, 2014)
Given the importance of the food industry in economic and social growth of the society as a whole , as well as social and strategic role of bakery industry particularly important and urgent task is the timely detection of problems in the functioning of the industry and identify ways to solve them in order to further develop and enhance competitiveness.
Keywords: bread; flou; bakery; хліб; борошно; пекарня; кафедра іноземних мов професійного спрямування